Cell-based high-throughput screening of cationic polymers for efficient DNA and siRNA delivery. (1st October 2020) - Wu, Yihang; Wang, Ling; Xiong, Yue; Zhou, Quanming; Li, Linxian; Chen, Guanyu; Ping, Yulei; Davidson, Gary; Levkin, Pavel A.; Gao, Liqian; Deng, Wenbin
Abstract: Development of non-viral gene vectors which can efficiently and safely transfect plasmid DNA and siRNA into cells is of great importance for gene therapy. Despite lots of efforts spent, it is still imperative to develop suitable gene vectors with better transfection efficiency and low cytotoxicity. To this end, we successfully designed, synthesized and screened a library of 120 polymers ( via nucleophilic substitution reaction between dihalides and amines). With cell-based transfection screening assays, 120 polymers were tested to evaluate their transfection efficiency of transporting DNA and siRNA into cells. Our results indicated that hydrophobic modification could greatly enhance cationic polymers' transfection efficiency, and polymers with long linkers usually showed better transfection performance, especially for polymers with the linker of 1, 12-dibromododecane (L3 linker). Besides, polyalkylamines exhibited better transfection efficiency with the polymer particle size around 200 nm and the zeta potential in the range of + 40 mV to +50 mV. Interestingly, polymer particles made from N15HL3 not only exhibited better DNA transfection efficiency in HEK 293T cells but also showed higher siRNA transfection efficiency in U87 Luc-GFP cells together with low cell toxicity than Lipofectamine 2000 (one of commercial transfection reagents). Therefore, it is hoped that our study here not only provides promising gene vector candidates for further evaluation in gene therapy, but also provides valuable insights for better understanding of the relationship between the chemical structures and gene transfection efficiency to rationally design better non-viral gene vectors for gene therapy in the future. Graphical abstract: Image, graphical abstract